Family characteristics of low income bornes that contribute to under achievement or school failure in children - Jadue, Gladys (1996)
This article shows the more salient characteristics in bornes from low economic status, which affect children's normal cognitive and psychosocial development as well as their school performance. It is suggested that in order to improve children's chance for a better performance at school, mothers should be trained in strategies and practices to assist in the learning process their children to successfully achieve their goals.